2004
DOI: 10.1136/bjo.2003.039917
|View full text |Cite
|
Sign up to set email alerts
|

An intravitreal biodegradable sustained release naproxen and 5-fluorouracil system for the treatment of experimental post-traumatic proliferative vitreoretinopathy

Abstract: Background/aims: To determine the potential of an intravitreal sustained release naproxen and 5-fluorouracil (NA/ 5-FU) codrug for the treatment of experimental proliferative vitreoretinopathy (PVR) in a model for trauma associated tractional retinal detachment (TRD). Methods: Sustained release pellets were prepared by covalently linking naproxen to 5-fluorouracil. Drug release was tested in vitro and toxic effects were evaluated by electroretinography and light microscopy. Traumatic PVR was induced in pigment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 19 publications
(8 reference statements)
0
25
0
2
Order By: Relevance
“…Finally, Kivilcim et al [60] showed that in silicone-filled eyes, the safe dose is up to 200 g, and therefore the vitreous status is important to know before intravitreal administration of 5-FU. In another study, Cardillo et al [61] designed a sustained-release pellet of 1.5 mg naproxen and 5-FU with continuous drug delivery. In this study, there were no drug-related toxic effects evident on histopathological or ERG examination of eyes containing the naproxen/5-FU pellet [61] .…”
Section: Antiviral Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Kivilcim et al [60] showed that in silicone-filled eyes, the safe dose is up to 200 g, and therefore the vitreous status is important to know before intravitreal administration of 5-FU. In another study, Cardillo et al [61] designed a sustained-release pellet of 1.5 mg naproxen and 5-FU with continuous drug delivery. In this study, there were no drug-related toxic effects evident on histopathological or ERG examination of eyes containing the naproxen/5-FU pellet [61] .…”
Section: Antiviral Agentsmentioning
confidence: 99%
“…In another study, Cardillo et al [61] designed a sustained-release pellet of 1.5 mg naproxen and 5-FU with continuous drug delivery. In this study, there were no drug-related toxic effects evident on histopathological or ERG examination of eyes containing the naproxen/5-FU pellet [61] .…”
Section: Antiviral Agentsmentioning
confidence: 99%
“…Therefore, in addition to a clinical indirect microscopic examination, a detailed fundus evaluation of the enucleated eye under a dissecting microscopy is used for PVR grading as follows [86]:…”
Section: Classification Of Animal Pvr In Pharmaceutical Investigationsmentioning
confidence: 99%
“…[65]. Their results suggested that this codrug system effectively inhibits the progression of experimental proliferative vitreoretinopathy (PVR) in a rabbit trauma model that closely resembles PVR in humans [66]. This unique concept of codrug design has also been utilized in our laboratories for codrugs of ethacrynic acid (ECA) covalently linked to either atenolol (ATL) or timolol (TML) via ester bond linkages ( Figure 4) were designed and synthesized to improve ocular delivery, and in addition, to take advantage of the apparent synergistic mechanism of ECA and the two β-adrenergic receptor antagonists [67].…”
Section: B the Codrug Approachmentioning
confidence: 98%